Ideological Discourse: Based on Subjective Conditions Towards Objective Consciousness of Intellectuals Understanding Reality Sociological Perspective of Knowledge - Surahman, Surahman; Maula, Hajir Bahrun; Wijaya, Nanang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2025)
The sociology of knowledge examines how the subjective thoughts and ideological backgrounds of intellectuals influence their perception and understanding of reality. Ideological biases often shape their analysis, creating a gap between perceived and objective truth. This study aims to explore how these subjective conditions affect the ability of intellectuals to attain objective consciousness and the development of scientific knowledge within the framework of the sociology of knowledge. Employing a phenomenological qualitative approach, the research captures perceptions through interpretive analysis, drawing on the theories of Karl Mannheim and Clifford Geertz to analyze the interaction between cultural systems, ideology, and knowledge construction. The findings reveal that ideological influences significantly shape how intellectuals interpret facts and social phenomena, often leading to partial or biased understandings that hinder objectivity. The sociology of knowledge serves as a crucial tool in unveiling these subjective influences, encouraging self-awareness among researchers regarding their social and cultural conditioning. The conclusion emphasizes that achieving objective consciousness necessitates an awareness of the social and ideological factors that shape perceptions. The discipline offers vital insights into the relationship between subjective beliefs and objective realities, advocating for reflexivity and contextual understanding in scientific inquiry to foster a more accurate and comprehensive grasp of social phenomena.